Hubungan Status Gizi Dengan Keseimbangan Anak Usia 4-5 Tahun Di PG/TK Lumen Christi School Surabaya - Anastasia Putu Martha; Raditya Kurniawan Djoar (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To analyzed the relationship of nutritional status with the balance of children aged 4-5 years at PG/TK Lumen Christi School SurabayaMethods: This research design is analytic observational with cross sectional approach.Results: Involving 22 children aged 4-5 years at PG/TK Lumen Christi School Surabay . Sampling technique using total sampling method. Existing data were analyzed using Pearson’s Test with significant level of 0.05. Statistical test results obtained that nutritional status did not had a relationship with balance because p> 0.05Conclusion: Nutritional status did not related to the balance of children aged 4-5 years